The Relationship Between Numeracy Literacy and Self-Efficacy with Students' Science Learning Outcomes in Grade VII - Bela Yurita; Dios Sarkity; Elfa Oprasmani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Numeracy literacy is one of the essential competencies students need to develop to face future challenges. This research investigates the relationship between numeracy literacy and academic achievement, self-efficacy and academic achievement, as well as the combined influence of numeracy literacy and self-efficacy on eighth-grade students' learning outcomes. Using a quantitative correlational design, the study involved 198 students from a total population of 414 at SMPN 4 Tanjungpinang, selected via stratified random sampling. Data analysis employed Pearson’s product-moment correlation for both simple and multiple correlation tests. The research tools included a numeracy literacy test, a self-efficacy questionnaire, and science performance documentation. The results showed a moderate positive link between numeracy literacy and academic performance (r = 0.482). A very strong correlation was found between self-efficacy and performance (r = 0.915). Moreover, the combined relationship between numeracy literacy and self-efficacy in relation to learning outcomes was also very strong (r = 0.957). These results highlight the need to enhance numeracy skills in schools by applying effective teaching strategies.